2003
DOI: 10.1002/jemt.10337
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of ACTH: Beyond cAMP

Abstract: ACTH is the major regulator of adrenal cortex function, having acute and chronic effects on steroid synthesis and secretion. The precise molecular mechanisms by which ACTH stimulates steroid synthesis and secretion, as well as cell hypertrophy, survival, and migration are still poorly understood. Several studies have shown that ACTH action is mediated not only by cyclic adenosine monophosphate (cAMP), but also by calcium (Ca(2+)), both interacting closely through positive feedback loops to enhance steroid secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 145 publications
1
82
0
Order By: Relevance
“…One possibility includes a PRLinduced promotion of adrenal steroidogenesis. It is well known that ACTH regulates glucocorticoid secretion through the cyclic AMP (cAMP) pathway [31][32][33][34][35][36][37]. It has been shown that the action of PRL might be mediated through G-protein-adenylate cyclase coupling and cAMP production [38,39], where in chronic hyperprolactinemia enhances receptor-G-protein-adenylate cyclase coupling and cAMP production [2].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility includes a PRLinduced promotion of adrenal steroidogenesis. It is well known that ACTH regulates glucocorticoid secretion through the cyclic AMP (cAMP) pathway [31][32][33][34][35][36][37]. It has been shown that the action of PRL might be mediated through G-protein-adenylate cyclase coupling and cAMP production [38,39], where in chronic hyperprolactinemia enhances receptor-G-protein-adenylate cyclase coupling and cAMP production [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although the regulation of aldosterone production by cAMP and Ca 2ϩ is summarized in recent reviews (19,37,46), the downstream signaling of both second messengers is controversial and far from being completely resolved. One of the reasons for controversial data may be connected with the fact that some of the signaling mechanisms generated by cAMP and Ca 2ϩ (activation of MAPKs, PKC, or small GTPases) may be more responsible for other cellular functions, such as proliferation or migration of ZG cells, than directly involved in acute stimulation of aldosterone production.…”
Section: Discussionmentioning
confidence: 99%
“…Many hormonal and paracrine factors are involved in the regulation of aldosterone production; however, under physiological conditions, the most important ones are adrenocorticotropin (ACTH), angiotensin II (ANG II), and extracellular K ϩ (19,46). The main action of ACTH in ZG cells is connected with the activation of transmembrane G s ␣-coupled ACTH receptors and the generation of cAMP as a second messenger (11,37).…”
mentioning
confidence: 99%
“…ACTH as a key regulator of adrenal gland growth and function affects several intracellular signaling cascades which have been reviewed (Gallo-Payet & Payet 2003, Forti et al 2006, Otis et al 2007b) and which cannot be discussed here in a comprehensive manner. Concerning the effects of ACTH on ERK activation, positive (Le & Schimmer 2001, Ferreira et al 2004, McNeill et al 2005, weak (Lotfi et al 1997, Lepique et al 2000, negative ( Watanabe et al 1997), or no effects have been described (Cote et al 1998).…”
Section: Effectors Of Erk1/2 Activation In Adrenocortical Cellsmentioning
confidence: 99%